Molecular epidemiology of clinical filamentous fungi in Qatar beyond Aspergillus and Fusarium with notes on the rare species. (2nd January 2023) - Salah, Husam; Houbraken, Jos; Boekhout, Teun; Almaslamani, Muna; Taj-Aldeen, Saad J
Abstract: Due to an increasing number of patients at risk (i.e., those with a highly compromised immune system and/or receiving aggressive chemotherapy treatment), invasive fungal infections (IFI) are increasingly being reported and associated with high mortality rates. Aspergillus spp., particularly A. fumigatus, is the major cause of IFI caused by filamentous fungi around the world followed by Fusarium spp., however, other fungi are emerging as human pathogens. The aim of this study was to explore the epidemiology and prevalence of the non- Aspergillus and non- Fusarium filamentous fungi in human clinical samples over an 11-year period in Qatar using molecular techniques. We recovered 53 filamentous fungal isolates from patients with various clinical conditions. Most patients were males (75.5%), 9.4% were immunocompromised, 20.7% had IFI, and 11.3% died within 30 days of diagnosis. The fungal isolates were recovered from a variety of clinical samples, including the nasal cavity, wounds, respiratory samples, body fluids, eye, ear, tissue, abscess, and blood specimens. Among the fungi isolated, 49% were dematiaceous fungi, followed by Mucorales (30%), with the latter group Mucorales being the major cause of IFI (5/11, 45.5%). The current study highlights the epidemiology and spectrum of filamentous fungal genera, other than Aspergillus and Fusarium, recovered from human clinical samples in Qatar, excluding superficial infections, which can aid in the surveillance of uncommon and emerging mycoses. Lay Summary: We recovered 53 non- Aspergillus and non- Fusarium filamentous fungal isolates from 53 patients in Qatar. Dematiaceous (black) fungi were the most isolated fungi followed by Mucorales, with the latter group Mucorales being the major cause of invasive infections in this study.